Interaction between economy and environment: a theoretical discussion - Menuzzi, Tamara Silvana; Silva, Luiz Gustavo Zuliani (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This work intends to present a brief discussion on some fundamental issues between Economy and Ecology, trying to analyze thetwo main theoretical chains of the economic science regarding the environment: the environmental economy and the ecological economy. The imperfections left by the environmental economy theory, of neoclassical origin, and the concern on environmental problems of the modern world, request urgency in the revision of many economic concepts, in search of a new way to think the connections between economy and nature. From the moment that the economic system created by the man is no longer compatible with the ecological system offered by the nature, generating serious environmental crises, it is necessary a new adaptation of these relations. Thus the ecological economy appears, bringing great contributions and opening ways that make the construction of new relations between economy and ecology possible.